Material parametric optimisation of wing leading edge profile against soft body impact. Issue 3 (4th May 2022) - Mol, S. Kavitha; Sadiq, A.
Abstract: The present study aims to optimise the material parameters of the 2xxx series aluminium alloy used in aircraft wing leading edges to improve its mechanical properties against bird impact. For this study, a bird model is established and validated with an experiment test from literature and with a bird strike test on the wing leading edge. The significant material parameters which affect the energy absorption characteristics of the wing leading edge is selected from the comparison of parametric study results. Then the selected parameters are optimised and validated with bird impact analysis studies based on Taguchi's L16 factorial design of experiments combined with grey relational analysis. The significant improvement in the mechanical properties, i.e. yield strength, ultimate tensile strength, and tensile toughness of the new optimised aluminium alloy has been proved with a series of uniaxial tension tests. The new alloy shows average property improvement up to 24.44% in tensile toughness and 19.4% in tensile strength than baseline alloy AA 2024-T3.